Telomere maintenance requires the RAD51D recombination/repair protein. - Tarsounas, M; Muñoz, P; Claas, A; Smiraldo, P; Pittman, D; Blasco, M; West, S (2004)
The five RAD51 paralogs (RAD51B, RAD51C, RAD51D, XRCC2, and XRCC3) are required in mammalian cells for normal levels of genetic recombination and resistance to DNA-damaging agents. We report here that RAD51D is also involved in telomere maintenance. Using immunofluorescence labeling, electron microscopy, and chromatin immunoprecipitation assays, RAD51D was shown to localize to the telomeres of both meiotic and somatic cells. Telomerase-positive Rad51d(-/-) Trp53(-/-) primary mouse embryonic fibroblasts (MEFs) exhibited telomeric DNA repeat shortening compared to Trp53(-/-) or wild-type MEFs. Moreover, elevated levels of chromosomal aberrations were detected, including telomeric end-to-end fusions, a signature of telomere dysfunction. Inhibition of RAD51D synthesis in telomerase-negative immortalized human cells by siRNA also resulted in telomere erosion and chromosome fusion. We conclude that RAD51D plays a dual cellular role in both the repair of DNA double-strand breaks and telomere protection against attrition and fusion.